2009
DOI: 10.1111/j.1440-1843.2009.01531.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of a superoxide dismutase/catalase mimetic compound against paraquat pneumotoxicity in rat lung

Abstract: EUK-134, a superoxide dismutase/catalase mimetic compound decreased the pneumotoxic effect of paraquat in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Preclinical studies have shown that intraperitoneal (i.p.) administration of EUK-134 prevented HSOS, attenuated kainate-induced neuropathology and protected against paraquat pneumotoxicity in rat models at a dose of 10 mg/kg body weight (Rong et al, 1999; Shopova et al, 2009). EUK-134 at a dose of 12.5 mg/kg body weight every other day seems to be most effective in our wound healing studies.…”
Section: Methodsmentioning
confidence: 99%
“…Preclinical studies have shown that intraperitoneal (i.p.) administration of EUK-134 prevented HSOS, attenuated kainate-induced neuropathology and protected against paraquat pneumotoxicity in rat models at a dose of 10 mg/kg body weight (Rong et al, 1999; Shopova et al, 2009). EUK-134 at a dose of 12.5 mg/kg body weight every other day seems to be most effective in our wound healing studies.…”
Section: Methodsmentioning
confidence: 99%
“…It may be argued that a subset of these symptoms (e.g. impaired gait, reduced locomotion, and poor posture) stem from a systemic toxicity following paraquat, given that paraquat does affect peripheral organ functioning, most notable the lungs (Shopova et al, 2009;Suntres, 2002). However, if the current paraquat paradigm induced such systemic toxicity, it would be expected that mice would display signs of general illness and respiratory dysfunction.…”
Section: Vehiclementioning
confidence: 99%